COST ANALYSIS OF PATIENTS WITH SQUAMOUS CELL CERVICAL CANCER STAGE IIB-IIIB WITH PACLITAXEL CISPLATIN CHEMOTHERAPY FROM THE SOCIETAL PERSPECTIVE - Ekayanti, Ni Kd Rintan Listiani; Noviyani, Rini; Yowani, Sagung Chandra; Ariawati, Ketut; Budiana, I Nyoman G. (Journal Pharmaceutical Science and Application; Vol 5 No 1 (2023): Journal Pharmaceutical Science and Application (JPSA)DO - 10.24843/JPSA.2023.v05.i01.p05, 2023)
Background: The high prevalence of cervical cancer patients and the variety of necessary expenses needed causing financial hardship to both the patient and hospital. Furthermore, the disparity between the INA-CBGs rates and the costs of treatment incurred by hospitals and the limited information regarding the costs of cervical cancer undergoing cisplatin paclitaxel chemotherapy as viewed from a societal perspective were the reasons to conduct this research. Objective: The aim of this study was to determine the cost of squamous cell cervical cancer patients at stage IIB-IIB who received cisplatin paclitaxel chemotherapy from a social perspective. So in this study the difference in costs is used to calculate costs from a hospital perspective. Methods: This research was an observational study with a prospective incidence approach and consecutive sampling as the sampling method. This research was conducted from January to June 2017 at Sanglah General Hospital, Denpasar. Cost data from a societal perspective for six chemotherapy series were obtained from the Claim Guarantee Installation, Fund Mobility Section, interviews and filling in the logbook by patients and then calculated using the micro-costing method. Results: The results of this study obtained five patients who met the inclusion criteria. From the perspective of BPJS Kesehatan, the average cost of cervical cancer with paclitaxel cisplatin chemotherapy was IDR 24.703.470,00. From a hospital perspective, the average cost of cervical cancer with paclitaxel cisplatin chemotherapy was IDR 6.619.204,00., and from the perspective of patients and their families, the average burden of costs for cervical cancer with paclitaxel cisplatin chemotherapy was IDR 9.149.300,00. Conclusion: Cost analysis on five squamous cell cervical cancer patients with stage IIB-IIIB with six series of paclitaxel cisplatin chemotherapy viewed from the perspective of BPJS Kesehatan, hospital was IDR 24,703,470.00, IDR 6,619,204.00, and IDR 9,149,300.00, respectively. Keywords: Cervical Cancer; Chemotherapy; Cost Analysis; Paclitaxel Cisplatin; Societal Perspective